Lithium boron carbon-coated lithium-rich lithium iron phosphate anode lithium supplement material, preparation method and application thereof
Patent Information
- Application Number
- CN202311216260.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-19
AI Technical Summary
[0004]本发明的主要目的在于提供一种锂硼碳包覆的富锂铁酸锂正极补锂材料及其制备方法和应用,以解决现有技术中富锂铁酸锂材料本征离子和电子电导率较低,且结构稳定性差表面残碱高,导致其加工应用难度较大,极化较大,倍率性能不佳,难以发挥高补锂容量以应对高功率电池需求
[0020]应用本申请的技术方案,本申请提供的锂硼碳包覆的富锂铁酸锂正极补锂材料在富锂铁酸锂颗粒的表面包覆锂硼碳层,不仅二维片状结构的锂硼碳包覆层能够增加比表面积,促进材料与电解液接触,进一步提升锂离子的传输效率,提高倍率性能,而且由于锂碳硼包覆层本征结构是由交替排列的六边形蜂窝状硼碳层及在其中心的锂原子层组成,脱锂态会产生空穴掺杂效应,能够进一步提升容量,同时还能够提升材料的结构稳定性,降低残碱,进而发挥高补锂容量满足高功率电池需求。
Smart Images

Figure CN117239083B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode lithium replenishment materials technology, and more specifically, to a lithium-boron-carbon coated lithium-rich lithium ferrite cathode lithium replenishment material, its preparation method, and its application. Background Technology
[0002] Lithium-replenishing materials refer to materials added to the electrode material before a lithium-ion battery begins operation, which can release a large amount of lithium. + Lithium-rich lithium iron phosphate (Li5FeO4) is used to compensate for irreversible lithium loss caused by the formation of the SEI film, thereby improving the overall capacity and energy density of the battery. As a high-capacity cathode lithium supplement, it has attracted increasing attention. Theoretically, each mole of Li5FeO4 can provide 5 Li ions. + With a specific capacity as high as 867 mAh / g, the energy density and cycle performance of lithium-ion batteries can be significantly improved by incorporating a certain amount of Li5FeO4 as a lithium replenishment additive into traditional cathode materials. However, lithium-rich lithium iron phosphate materials have low intrinsic ionic and electronic conductivity, poor structural stability, and high surface alkali residue, making them difficult to process and apply. They also exhibit high polarization, poor rate performance, and are unable to achieve high lithium replenishment capacity to meet the demands of high-power batteries.
[0003] In view of this, the present invention is hereby proposed. Summary of the Invention
[0004] The main objective of this invention is to provide a lithium-boron-carbon coated lithium iron oxide cathode material for lithium replenishment, its preparation method, and its application. This addresses the problems of existing lithium iron oxide materials, which have low intrinsic ionic and electronic conductivity, poor structural stability, and high surface alkali residue, resulting in difficulties in processing and application, large polarization, poor rate performance, and difficulty in achieving high lithium replenishment capacity to meet the demands of high-power batteries.
[0005] To achieve the above objectives, according to one aspect of the present invention, a lithium boron carbon-coated lithium iron ferrite positive and negative material is provided, comprising lithium iron ferrite particles, wherein the surface of the lithium iron ferrite particles is coated with a lithium boron carbon layer, wherein the average size of the lithium iron ferrite particles is 1 to 10 μm, and the thickness of the lithium boron carbon layer is 100 to 500 nm.
[0006] According to another aspect of the present invention, a method for preparing the above-mentioned lithium-boron-carbon coated lithium iron ferrite cathode lithium replenishment material is provided. The preparation method includes: step S1, mixing a lithium source, a boron source and a carbon source by ball milling once to obtain a lithium-boron-carbon precursor mixture; step S2, mixing lithium iron ferrite particles with the lithium-boron-carbon precursor mixture by ball milling a second time to obtain a cathode lithium replenishment material precursor; and step S3, sintering the cathode lithium replenishment material precursor at high temperature to obtain the lithium-boron-carbon coated lithium iron ferrite cathode lithium replenishment material.
[0007] Further, in step S1, the molar ratio of lithium source, boron source and carbon source is 1:1:1, based on the molar amounts of lithium, boron and carbon.
[0008] Furthermore, the lithium source is lithium hydride, and more preferably, the average particle size of lithium hydride is ≤2μm.
[0009] Furthermore, the boron source is boron powder, and more preferably, the average particle size of the boron powder is ≤500nm.
[0010] Furthermore, the carbon source is carbon powder, and more preferably, the average particle size of the carbon powder is ≤500nm.
[0011] Further, in step S1, the rotation speed of the ball mill is 600-1000 r / min, the ball milling medium is zirconium oxide, the ball-to-material ratio is 5-10:1, and the ball milling time is 1-3 h.
[0012] Further, in step S2, the mass ratio of lithium iron phosphate particles to the lithium boron carbon precursor mixture is 1:(0.01~0.031).
[0013] Further, in step S2, the rotation speed of the secondary ball mill is 600-1000 r / min, the ball milling medium is zirconium oxide, the ball-to-material ratio is 2-10:1, and the ball milling time is 5-10 h.
[0014] Further, in step S3, the high-temperature sintering temperature is 1500–2000℃, and the time is 1–3 hours.
[0015] Further, in step S3, the cathode lithium replenishment material precursor is placed in a niobium crucible and sintered at high temperature in an induction coil under inert gas protection, and then cooled to obtain the lithium boron carbon-coated lithium iron ferrite cathode lithium replenishment material.
[0016] Furthermore, the high-temperature sintering is carried out under the protection of an inert gas, which includes at least one of nitrogen or argon.
[0017] Furthermore, the cooling rate is 1–3 °C / min, and the cooling is carried out under inert gas protection.
[0018] According to a third aspect of the present invention, the application of the lithium boron carbon-coated lithium-rich lithium ferrite cathode supplemental material provided in the first aspect or the lithium boron carbon-coated lithium-rich lithium ferrite cathode supplemental material obtained according to the preparation method provided in the second aspect in a lithium-ion battery is provided.
[0019] According to a fourth aspect of the present invention, a lithium-ion battery is provided, the lithium-ion battery comprising a lithium boron carbon-coated lithium-rich lithium ferrite positive electrode supplementing material provided in the first aspect or a lithium boron carbon-coated lithium-rich lithium ferrite positive electrode supplementing material obtained according to the preparation method provided in the second aspect.
[0020] Applying the technical solution of this application, the lithium boron carbon-coated lithium iron phosphate cathode replenishment material provided by this application has a lithium boron carbon layer coated on the surface of lithium iron phosphate particles. Not only can the two-dimensional sheet-like lithium boron carbon coating layer increase the specific surface area, promote the contact between the material and the electrolyte, and further improve the lithium-ion transport efficiency and rate performance, but also, since the intrinsic structure of the lithium carbon boron coating layer is composed of alternating hexagonal honeycomb boron carbon layers and lithium atom layers at its center, the delithiation state will generate a hole doping effect, which can further improve the capacity. At the same time, it can also improve the structural stability of the material, reduce residual alkali, and thus achieve high replenishment capacity to meet the requirements of high-power batteries. Attached Figure Description
[0021] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0022] Figure 1 SEM images of the positive electrode lithium replenishment materials provided in Embodiment 1 (Fig. a) and Comparative Example 1 (Fig. b) according to the present invention are shown. Detailed Implementation
[0023] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0024] As analyzed in the background section of this application, incorporating a certain amount of Li5FeO4 as a lithium supplementation additive into traditional cathode materials can significantly improve the energy density and cycle performance of lithium-ion batteries. However, due to the low intrinsic ionic and electronic conductivity, poor structural stability, and high surface alkali residue of lithium-rich lithium iron phosphate materials, their processing and application are difficult, resulting in significant polarization, poor rate performance, and difficulty in achieving high lithium supplementation capacity to meet the demands of high-power batteries. To address this issue, this application provides a lithium boron carbon-coated lithium-rich lithium iron phosphate cathode lithium supplementation material, its preparation method, and its application.
[0025] In a first typical embodiment of this application, a lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material is provided. The positive electrode lithium replenishment material includes lithium iron ferrite particles, the surface of which is coated with a lithium boron carbon layer. The average size of the lithium iron ferrite particles is 1 to 10 μm, and the thickness of the lithium boron carbon layer is 100 to 500 nm.
[0026] The lithium boron carbon-coated lithium iron ferrite cathode replenishment material provided in this application coats the surface of lithium iron ferrite particles with a lithium boron carbon layer. This not only increases the specific surface area by utilizing the two-dimensional sheet-like structure of the lithium boron carbon coating, promoting the contact between the material and the electrolyte and further improving the lithium-ion transport efficiency and rate performance, but also, because the intrinsic structure of the lithium carbon boron layer consists of alternating hexagonal honeycomb boron carbon layers and lithium atom layers at its center, the delithiation state will generate a hole doping effect, which can further improve the capacity. At the same time, it can also improve the structural stability of the material, reduce residual alkali, and thus achieve high replenishment capacity to meet the requirements of high-power batteries.
[0027] In the lithium-boron carbon-coated lithium-rich lithium iron ferrite cathode lithium replenishment material provided in this application, the average size of the lithium-rich lithium iron ferrite particles is, for example, 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm or any two of these values; the thickness of the lithium boron carbon layer is, for example, 100 μm, 150 μm, 200 μm, 300 μm, 400 μm, 500 μm or any two of these values.
[0028] In a second typical embodiment of this application, a method for preparing a lithium-boron-carbon coated lithium iron ferrite cathode material is also provided. The preparation method includes: step S1, mixing a lithium source, a boron source, and a carbon source by ball milling once to obtain a lithium boron-carbon precursor mixture; step S2, mixing lithium iron ferrite particles with the lithium boron-carbon precursor mixture by ball milling a second time to obtain a cathode material precursor; and step S3, sintering the cathode material precursor at high temperature to obtain a lithium boron-carbon coated lithium iron ferrite cathode material.
[0029] The method for preparing lithium-rich lithium iron phosphate cathode material with lithium boron carbon coating provided in this application combines primary ball milling, secondary ball milling, and high-temperature sintering to uniformly coat the surface of lithium-rich lithium iron phosphate particles with a two-dimensional sheet-like lithium boron carbon layer. This not only improves the structural stability of the material and reduces residual alkali, but also increases the specific surface area, promotes the contact between the material and the electrolyte, further improves the lithium-ion transport efficiency, and enhances the rate performance. At the same time, it also generates a hole doping effect, further increasing the capacity and effectively meeting the requirements of high-power batteries.
[0030] In step S1 above, in order to facilitate the generation of a two-dimensional sheet-like lithium-boron-carbon layer, it is preferable that the molar ratio of lithium source, boron source and carbon source is 1:1:1 based on the molar amount of lithium-boron-carbon.
[0031] The above-mentioned molar amounts of lithium, boron, and carbon refer to the lithium source being measured in molar amounts of lithium, the boron source in molar amounts of boron, and the carbon source in molar amounts of carbon.
[0032] The specific type of lithium source is not limited; any lithium-containing compound that generates lithium during the subsequent sintering process is acceptable. However, to avoid the introduction of impurity atoms, lithium hydride is preferred as the lithium source. To further improve the efficiency of the first ball milling, the average particle size of lithium hydride is preferably ≤2μm.
[0033] The specific type of boron source is not limited; any boron-containing compound generated during the subsequent sintering process is acceptable. However, to avoid the introduction of impurity atoms, boron powder is preferred as the boron source. To further improve the efficiency of the single ball milling, the average particle size of the boron powder is preferably ≤500 nm.
[0034] The specific type of carbon source is not specifically limited; any carbon-containing compound that generates carbon during the subsequent sintering process is acceptable. However, to avoid the introduction of heteroatoms, carbon powder is preferred as the carbon source. To further improve the efficiency of the single ball milling, the average particle size of the carbon powder is preferably ≤500 nm.
[0035] In some embodiments, in step S1 above, to further improve the efficiency of the single ball milling, the preferred single ball milling speed is 600-1000 r / min, the milling media is zirconium oxide, the ball-to-material ratio is 5-10:1, and the milling time is 1-3 h. Single ball milling allows for a more uniform mixing of the lithium source, carbon source, and boron source.
[0036] Typically, but not limitingly, in step S1, the rotational speed of the ball mill is 600 r / min, 650 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, or any range of two values; the ball-to-material ratio is 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or any range of two values; and the ball milling time is 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or any range of two values.
[0037] To facilitate the coating of the lithium-rich lithium iron ferrite particles with a lithium boron carbon layer of 100–500 nm thickness on the surface, the preferred mass ratio of the lithium-rich lithium iron ferrite particles to the lithium boron carbon precursor mixture is 1:(0.01–0.031), such as 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.031, or any range of two values.
[0038] In other embodiments, in step S2, in order to further improve the efficiency of the secondary ball milling, the preferred rotation speed of the secondary ball milling is 600-1000 r / min, the ball milling medium is zirconium oxide, the ball-to-material ratio is 2-10:1, and the ball milling time is 5-10 h.
[0039] Typically, but not limitingly, in step S1, the rotational speed of the secondary ball mill is 600 r / min, 650 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, or any range of two values; the ball-to-material ratio is 2:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or any range of two values; and the ball milling time is 5 h, 5.5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or any range of two values.
[0040] To facilitate the formation of a uniform and dense lithium boron carbon coating layer on the surface of lithium iron phosphate particles, the high-temperature sintering temperature in step S3 is preferably 1500–2000℃ (e.g., 1500℃, 1600℃, 1700℃, 1800℃, 1900℃, 2000℃ or any range of two values), and the time is 1–3h (e.g., 1h, 1.5h, 2h, 2.5h, 3h or any range of two values).
[0041] To further improve the uniformity and density of the lithium-boron-carbon layer, step S3 preferably includes: placing the cathode lithium supplement material precursor in a niobium crucible, sintering it at high temperature in an induction coil under inert gas protection, and then cooling it down to obtain a lithium-boron-carbon coated lithium-rich lithium iron ferrite cathode lithium supplement material. Employing an induction high-temperature sintering method simplifies the sintering process and reduces production costs.
[0042] To avoid introducing impurity atoms during high-temperature sintering, it is preferable to carry out high-temperature sintering under the protection of an inert gas, which includes, but is not limited to, any one or more mixed gases of nitrogen or argon.
[0043] To further improve the uniformity and density of the lithium boron carbon layer, the cooling process is preferably a slow cooling process with a cooling rate of 1 to 3 °C / min (such as 1 °C / min, 1.5 °C / min, 2 °C / min, 2.5 °C / min, 3 °C / min or any combination of two values), and the cooling is carried out under the protection of an inert gas.
[0044] In a third typical embodiment of this application, the application of the lithium boron carbon-coated lithium-rich lithium ferrite cathode supplemental material provided in the first typical embodiment or the lithium boron carbon-coated lithium-rich lithium ferrite cathode supplemental material obtained by the preparation method provided in the second typical embodiment is also provided in lithium-ion batteries.
[0045] The lithium boron carbon-coated lithium iron ferrite supplementation material provided in this application is beneficial to improving the stability of lithium-ion batteries, enhancing lithium-ion transport efficiency and rate performance, and further increasing capacity through hole doping effect, thereby achieving high supplementation capacity to meet high power requirements.
[0046] In a fourth typical embodiment of this application, a lithium-ion battery is also provided, which includes the lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material provided in the first typical embodiment above, or the lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material obtained by the preparation method provided in the second typical embodiment above.
[0047] The lithium-ion battery provided in this application uses lithium-boron-carbon coated lithium iron ferrite cathode material for lithium replenishment, which not only improves stability and service life, but also enhances lithium-ion transport efficiency and rate performance. At the same time, it further increases capacity through hole doping effect, thereby meeting high power requirements.
[0048] The beneficial effects of this application will be further illustrated below with reference to embodiments and comparative examples.
[0049] Example 1
[0050] This embodiment provides a lithium-boron-carbon coated lithium iron ferrite cathode material for lithium supplementation, which is prepared according to the following steps:
[0051] (1) 0.8g lithium hydride, 1.1g boron powder and 1.2g carbon powder were added to a ball mill jar in sequence, and zirconium oxide balls were added at a ball-to-material mass ratio of 5:1 for ball milling and mixing. The ball milling conditions were 600r / min and the ball milling time was 1h to obtain a lithium-boron-carbon precursor mixture; wherein, the average particle size of lithium hydride was ≤2μm; the average particle size of boron powder was ≤500nm; and the average particle size of carbon powder was ≤500nm.
[0052] (2) Add 100g of lithium-rich lithium iron oxide particles to the lithium boron carbon precursor mixture, add zirconium oxide balls at a material mass ratio of 5:1 and ball mill, the ball milling conditions are 600r / min and the ball milling time is 5h, to obtain the positive electrode lithium replenishment material precursor.
[0053] (3) The precursor of the positive electrode lithium replenishment material is transferred to a niobium crucible and placed in an induction coil for high-temperature sintering under argon protection. The sintering temperature is 1500℃ and the sintering time is 1h. Then, the temperature is slowly reduced at a rate of 1℃ / min to obtain the lithium boron carbon-coated lithium iron oxide positive electrode lithium replenishment material.
[0054] Example 2
[0055] This embodiment provides a lithium-boron-carbon coated lithium iron ferrite cathode material for lithium supplementation, which is prepared according to the following steps:
[0056] (1) 0.8g lithium hydride, 1.1g boron powder and 1.2g carbon powder were added to a ball mill jar in sequence, and zirconium oxide balls were added at a ball-to-material mass ratio of 10:1 for ball milling and mixing. The ball milling conditions were 1000r / min and the ball milling time was 1h to obtain a lithium-boron-carbon precursor mixture; wherein, the average particle size of lithium hydride was ≤2μm; the average particle size of boron powder was ≤500nm; and the average particle size of carbon powder was ≤500nm.
[0057] (2) Add 207g of lithium-rich lithium iron oxide particles to the lithium boron carbon precursor mixture, add zirconium oxide balls at a ball-to-material mass ratio of 5:1 and ball milling is carried out under the conditions of 600r / min and 10h to obtain the positive electrode lithium replenishment material precursor.
[0058] (3) The positive electrode lithium supplementation material precursor is transferred to a niobium crucible and placed in an induction coil for high-temperature sintering under argon protection. The sintering temperature is 2000℃ and the sintering time is 1h. Then, the temperature is slowly reduced at a rate of 2℃ / min to obtain the lithium boron carbon precursor mixture.
[0059] Example 3
[0060] This embodiment provides a lithium-boron-carbon coated lithium iron ferrite cathode material for lithium supplementation, which is prepared according to the following steps:
[0061] (1) 0.8g lithium hydride, 1.1g boron powder and 1.2g carbon powder were added to a ball mill jar in sequence, and zirconium oxide balls were added at a ball-to-material mass ratio of 10:1 for ball milling and mixing. The ball milling conditions were 800r / min and the ball milling time was 3h to obtain a lithium-boron-carbon precursor mixture; wherein, the average particle size of lithium hydride was ≤2μm; the average particle size of boron powder was ≤500nm; and the average particle size of carbon powder was ≤500nm.
[0062] (2) Add 310g of lithium-rich lithium iron oxide particles to the lithium boron carbon precursor mixture, add zirconium oxide balls at a ball-to-material mass ratio of 5:1 and ball milling is carried out under the conditions of 1000r / min and 6h to obtain the positive electrode lithium replenishment material precursor.
[0063] (3) The positive electrode lithium supplementation material precursor is transferred to a niobium crucible and placed in an induction coil for high-temperature sintering under argon protection. The sintering temperature is 1800℃ and the sintering time is 3h. Then, the temperature is slowly reduced at a rate of 3℃ / min to obtain the lithium boron carbon precursor mixture.
[0064] Example 4
[0065] This embodiment provides a lithium-boron-carbon coated lithium iron ferrite cathode material for lithium supplementation, which is prepared according to the following steps:
[0066] (1) 0.8g lithium hydride, 1.1g boron powder and 1.2g carbon powder were added to a ball mill jar in sequence, and zirconium oxide balls were added at a ball-to-material mass ratio of 5:1 for ball milling and mixing. The ball milling conditions were 1000r / min and the ball milling time was 3h to obtain a lithium-boron-carbon precursor mixture; wherein, the average particle size of lithium hydride was ≤2μm; the average particle size of boron powder was ≤500nm; and the average particle size of carbon powder was ≤500nm.
[0067] (2) Add 310g of lithium-rich lithium iron oxide particles to the lithium boron carbon precursor mixture, add zirconium oxide balls at a ball-to-material mass ratio of 5:1 and ball milling is carried out under the conditions of 800r / min and 10h to obtain the positive electrode lithium replenishment material precursor.
[0068] (3) The positive electrode lithium supplementation material precursor is transferred to a niobium crucible and placed in an induction coil for high-temperature sintering under argon protection. The sintering temperature is 1600℃ and the sintering time is 3h. Then, the temperature is slowly reduced at a rate of 1℃ / min to obtain the lithium boron carbon precursor mixture.
[0069] Example 5
[0070] This embodiment provides a lithium-boron-carbon coated lithium iron ferrite cathode material for lithium supplementation, which is prepared according to the following steps:
[0071] (1) 0.8g lithium hydride, 1.1g boron powder and 1.2g carbon powder were added to a ball mill jar in sequence, and zirconium oxide balls were added at a ball-to-material mass ratio of 5:1 for ball milling and mixing. The ball milling conditions were 600r / min and the ball milling time was 1h to obtain a lithium-boron-carbon precursor mixture; wherein, the average particle size of lithium hydride was ≤2μm; the average particle size of boron powder was ≤500nm; and the average particle size of carbon powder was ≤500nm.
[0072] (2) Add 100g of lithium-rich lithium iron oxide particles to the lithium boron carbon precursor mixture, add zirconium oxide balls at a ball-to-material mass ratio of 2:1, and ball mill the mixture. The ball milling conditions are 600r / min and the ball milling time is 5h to obtain the positive electrode lithium replenishment material precursor.
[0073] (3) The positive electrode lithium supplementation material precursor is transferred to a niobium crucible and placed in an induction coil under argon protection for high-temperature sintering at a temperature of 1500℃ for 1 hour. After natural cooling, a lithium boron carbon precursor mixture is obtained.
[0074] Example 6
[0075] The difference between this embodiment and embodiment 1 is that in step (2), the amount of lithium iron phosphate particles used is 400g.
[0076] Example 7
[0077] The difference between this embodiment and embodiment 1 is that in step (2), the amount of lithium iron phosphate particles used is 50g.
[0078] Example 8
[0079] The difference between this embodiment and embodiment 1 is that in step (2), the ball milling conditions are 1000 r / min and the ball milling time is 3 h.
[0080] Example 9
[0081] The difference between this embodiment and embodiment 1 is that in step (3), the high-temperature sintering is carried out directly in the niobium crucible and is not placed in the induction coil.
[0082] Example 10
[0083] The difference between this embodiment and embodiment 1 is that in step (3), the cooling rate is 5℃ / min.
[0084] Comparative Example 1
[0085] This comparative example provides a positive electrode lithium replenishment material, which is prepared according to the following steps: 100g of lithium-rich lithium iron phosphate particles are transferred to a niobium crucible, and under argon protection, they are placed in an induction coil for high-temperature sintering at a temperature of 1500℃ for 1h. Then, the temperature is slowly reduced at a rate of 1℃ / min to obtain the positive electrode lithium replenishment material.
[0086] Comparative Example 2
[0087] This comparative example provides a positive electrode lithium supplementation material, which is prepared according to the following steps:
[0088] (1) 0.8g lithium hydride, 1.1g boron powder, 1.2g carbon powder and 100g lithium iron ferrite particles were added to zirconium oxide balls at a ball-to-material mass ratio of 2:1 and ball-milled at 600r / min for 5h to obtain a lithium boron carbon precursor mixture; wherein the average particle size of lithium hydride is ≤2μm; the average particle size of boron powder is ≤500nm; and the average particle size of carbon powder is ≤500nm.
[0089] (2) The boron-carbon precursor mixture was transferred to a niobium crucible and placed in an induction coil under argon protection for high-temperature sintering at a temperature of 1500℃ for 1h. Then, the temperature was slowly reduced at a rate of 1℃ / min to obtain the positive electrode lithium replenishment material.
[0090] Experimental Example 1
[0091] The cathode lithium replenishment materials provided in Example 1 and Comparative Example 1 were examined using scanning electron microscopy (SEM), and their SEM images are shown below. Figure 1 As shown, (a) is a SEM image of the positive electrode lithium replenishment material provided in Example 1, and (b) is a SEM image of the positive electrode lithium replenishment material provided in Comparative Example 1. A comparison of (a) and (b) shows that the surface coating of the positive electrode lithium replenishment particles provided in Example 1 is a uniform and dense fine sheet-like structure with a coating thickness of approximately 300 nm, while the surface of the positive electrode lithium replenishment particles provided in Comparative Example 1 is exposed without a coating layer.
[0092] Experimental Example 2
[0093] The residual alkali (LiOH) content and specific surface area of the lithium-supplementing materials provided in the examples and comparative examples were determined, and the results are shown in Table 1 below.
[0094] Among them, (1) the method for determining the residual alkali (LiOH) content is as follows: accurately weigh 0.3g of sample into a 100ml clean and dry gas washing bottle, add 100ml of ethanol to the gas washing bottle and stir for 5min. After stirring, vacuum filter and collect the filtrate into a 100ml volumetric flask. Transfer 40ml of filtrate into a titration cup; titrate with 0.01M HCl standard solution to obtain the titration curve, and record the volume V1 of hydrochloric acid standard solution consumed in this process. At the same time, the analytical method blank is used, the volume V0 of hydrochloric acid consumed at the endpoint is recorded, and the LiOH content is 23.94×0.01×(V1-V0) / 120.
[0095] (2) The specific surface area was determined by the N2 adsorption-desorption tester and the material pretreatment temperature was 170℃.
[0096] In addition, the positive electrode lithium replenishment materials provided in the examples and comparative examples were used as positive electrode active materials to assemble coin cells of model CR2032. Then, the electrical performance was tested at a voltage range of 2V to 4.5V and a charge / discharge current of 0.05C and 0.1C. The results are shown in Table 1 below.
[0097] The CR2032 button cell is prepared according to the following steps: the positive electrode lithium replenishment material is mixed and ground with carbon black and PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1, and then coated onto aluminum foil as the positive electrode of the lithium-ion battery. The negative electrode of the battery is a lithium metal sheet, the separator is a polypropylene microporous membrane, the electrolyte is a 1 mol / L LiPF6 solution, and the electrolyte solvent is EC:DMC:EMC = 1:1:1 (v / v / v); then it is assembled in an argon-filled glove box.
[0098] Table 1
[0099]
[0100]
[0101] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects: The lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material provided in this application has a lithium boron carbon layer coated on the surface of lithium iron ferrite particles. Not only can the two-dimensional sheet-like lithium boron carbon coating layer increase the specific surface area and promote the contact between the material and the electrolyte, further improving the lithium ion transport efficiency and rate performance, but also, since the intrinsic structure of the lithium carbon boron coating layer is composed of alternating hexagonal honeycomb boron carbon layers and lithium atom layers at its center, the delithiation state will generate a hole doping effect, which can further improve the capacity. At the same time, it can also improve the structural stability of the material, reduce residual alkali, and thus achieve high lithium replenishment capacity to meet the requirements of high-power batteries.
[0102] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A lithium-boron-carbon coated lithium-rich lithium iron ferrite cathode material, characterized in that, The lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material includes lithium iron ferrite particles, the surface of which is coated with a lithium boron carbon layer, wherein the average size of the lithium iron ferrite particles is 1~10μm, and the thickness of the lithium boron carbon layer is 100~500nm. The preparation method of the lithium boron carbon-coated lithium iron ferrite cathode lithium supplementation material includes: Step S1: The lithium source, boron source and carbon source are ball-milled and mixed to obtain a lithium boron carbon precursor mixture; Step S2: The lithium iron oxide particles rich in lithium iron oxide are mixed with the lithium boron carbon precursor mixture by ball milling for a second time to obtain the positive electrode lithium supplementation material precursor. Step S3: The precursor of the positive electrode lithium replenishment material is sintered at high temperature to obtain the lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material. In step S1, the molar ratio of the lithium source, the boron source, and the carbon source is 1:1:1, based on the molar amounts of lithium, boron, and carbon. In step S3, the high-temperature sintering temperature is 1500~2000℃ and the time is 1~3h.
2. The method for preparing lithium-rich lithium iron phosphate cathode material with lithium boron carbon coating according to claim 1, characterized in that, The preparation method includes: Step S1: The lithium source, boron source and carbon source are ball-milled and mixed to obtain a lithium boron carbon precursor mixture; Step S2: The lithium iron oxide particles rich in lithium iron oxide are mixed with the lithium boron carbon precursor mixture by ball milling for a second time to obtain the positive electrode lithium supplementation material precursor. Step S3: The precursor of the positive electrode lithium replenishment material is sintered at high temperature to obtain the lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material.
3. The preparation method according to claim 2, characterized in that, Step S1, The lithium source is lithium hydride; And / or, the boron source is boron powder; And / or, the carbon source is toner.
4. The preparation method according to claim 2, characterized in that, In step S1, the rotation speed of the ball mill is 600~1000 r / min, the ball milling medium is zirconium oxide, the ball-to-material ratio is 5~10:1, and the ball milling time is 1~3 h.
5. The preparation method according to claim 2, characterized in that, In step S2, the mass ratio of the lithium iron ferrite particles to the lithium boron carbon precursor mixture is 1:(0.01~0.031).
6. The preparation method according to claim 2, characterized in that, In step S2, the rotation speed of the secondary ball mill is 600~1000 r / min, the ball milling medium is zirconium oxide, the ball-to-material ratio is 2~10:1, and the ball milling time is 5~10 h.
7. The preparation method according to claim 2, characterized in that, In step S3, the precursor of the positive electrode lithium replenishment material is placed in a niobium crucible and sintered at high temperature in an induction coil under inert gas protection, and then cooled to obtain the lithium boron carbon-coated lithium iron ferrite positive electrode lithium replenishment material.
8. The preparation method according to claim 7, characterized in that, In step S3, the high-temperature sintering is carried out under the protection of an inert gas, which includes at least one of nitrogen or argon. And / or, the cooling rate is 1~3℃ / min, and the cooling is carried out under inert gas protection.
9. The application of the lithium boron carbon-coated lithium-rich lithium ferrite cathode supplemental material according to claim 1 or the lithium boron carbon-coated lithium-rich lithium ferrite cathode supplemental material obtained by any one of claims 2 to 8 in a lithium-ion battery.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the lithium boron carbon-coated lithium-rich lithium ferrite cathode material as described in claim 1, or the lithium boron carbon-coated lithium-rich lithium ferrite cathode material prepared according to any one of claims 2 to 8.
Citation Information
Patent Citations
Polyanion composite material, its preparation method and application
CN102339999A
Lithium-supplementing additive for lithium-rich lithium ferrite positive electrode, preparation method of lithium-supplementing additive and lithium ion battery positive electrode
CN116706273A